If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6r + 7 = 13 + 7x Reorder the terms: 7 + 6r = 13 + 7x Solving 7 + 6r = 13 + 7x Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 6r = 13 + -7 + 7x Combine like terms: 7 + -7 = 0 0 + 6r = 13 + -7 + 7x 6r = 13 + -7 + 7x Combine like terms: 13 + -7 = 6 6r = 6 + 7x Divide each side by '6'. r = 1 + 1.166666667x Simplifying r = 1 + 1.166666667x
| 8x+4x=77 | | x(x-10)=7 | | (2y-1)=49 | | 8x+7x-2x+1x=12 | | (6-3i)(2+i)= | | 4x+19=93 | | 10+3x=5x-30 | | 12y-7y-8=87.25 | | 2x+13=7x-5 | | -1=7-8x | | -g+4=4-g | | h(t)=-16t^2+90t+2 | | 12=-50+20k-2k^2 | | 4r+4=4 | | 2(x-3)-3(x-4)=6-(x-6) | | 1x+12=25 | | (x+4)(5x-4)(2x-1)=0 | | (n)+1=2 | | .1x+.7y=-2.8 | | (x+2)(x+2)-12=36 | | (x-12)(x-4)=0 | | -4=1+r | | 2(m-7)(m-7)=16 | | 2x^4+9x^3+3x^2+36x-20=0 | | 7(n)=56 | | y(10y+11)=6 | | -5x+3y=24 | | 2(b-1)=2b+10 | | 2(64)+X=180 | | -p-4=-4-p | | -x^3+3x^2+6x-8=0 | | -2(6+6x)=8-8x |